Discovery and Timing of Four γ-Ray Millisecond Pulsars - M. Kerr; S. Johnston; C. J. Clark; F. Camilo; E. C. Ferrara; M. T. Wolff; S. M. Ransom; S. Dai; P. S. Ray; J. E. Reynolds; J. M. Sarkissian; E. D. Barr; et al. (The Astrophysical Journal)
We discovered four millisecond pulsars (MSPs) in searches of 80 γ -ray sources conducted from 2015 to 2017 with the Murriyang radio telescope of the Parkes Observatory. We provide an overview of the survey and focus on the results of a follow-up pulsar timing campaign. Using Fermi Large Area Telescope data, we have detected γ -ray pulsations from all four pulsars, and by combining radio and γ -ray data, we obtain improved timing solutions. We also provide flux density distributions for the radio pulsars and flux-calibrated and phase-aligned radio and γ -ray pulse profiles. Some of the pulsars may be suitable for radio pulsar timing array experiments. PSR J0646–5455, PSR J1803–4719, and PSR J2045–6837 are in typical, nearly circular white dwarf binaries with residual eccentricities proportional to their binary periods. PSR J1833–3840 is a black widow pulsar with the longest known period, P _b  = 0.9 day, and a very soft radio spectrum. PSR J0646–5455 has a strong, Vela-like γ -ray pulse profile and is suitable for inclusion in the γ -ray pulsar timing array. Despite this, it is possibly one of the lowest-efficiency γ -ray MSPs known. Indeed, all four new γ -ray MSPs have lower-than-average efficiency, a potential indication of bias in earlier searches. Finally, we retrospectively evaluate the efficiency of this survey: while only four new MSPs were directly discovered, subsequent campaigns have found pulsars in a further 19 of our targets, an excellent 30% efficiency.